Investigating an EFL pre-service teacher’s reflections during school teaching practice (ELT Forum: Journal of English Language Teaching, 2022)
Studies examining the reflective teaching practice of pre-service teachers in the context of EFL are still under-discussed as in Indonesia. Therefore, to fill this void, this study was conducted to identify the reflection of EFL pre-service teachers during teaching practice at schools. In practicing teaching, pre-service teachers face several challenges such as factors that influence the success of prospective teachers in teaching practice, lack of evaluation, and problem-solving in the classrooms with students. Therefore, through this research, the researchers try to examine the reflective teaching practice of an EFL pre-service teacher. This is a qualitative study using thematic analysis to analyse the data. The data were gathered from interviews and teaching journals. The finding shows that during the teaching practice, the participant’s experiences were reflected through five dimensions, i.e., philosophy, principles, theory, practice, and beyond practice. Overall, the results show that the participant’s beyond reflection remained the same with what she did in practice, and the themes that have been revealed from her reflections including the need to do a lot of preparation, having a variety of alternatives to minimize problems in the classroom, and the importance of students' success in understanding the material. The findings, therefore, are expected to provide insight to other EFL pre-service teachers to have reflective practices while conducting teaching practice.